Clinical profile of Otomycosis: a hospital based study at central terrain region of Nepal - Lageju, N; Shahi, SC; Goil, NK (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: Otomycosis is the fungal infection of ear with some complications involving middle ear cavity and mastoid cavity. It is one of commonly encountered problem in otolaryngology clinics. It is commonly present in hot, humid with moisture, high temperature. So, this research is to study the clinical profile of otomycosis in central terrain region of Nepal. Material and Methods: The study was conducted in department of ENT- head and neck surgery in Janaki medical college and teaching hospital from August 2015 to June 2016. All the clinically diagnosed cases were enrolled in the study with typical symptoms and characteristics fungal debris in the external auditory canal (EAC). All the data regarding age, sex, occupation, presenting complaints, type of fugal debris, presence of acute otitis externa, findings of tympanic membrane (TM) taken. Results: Total of 77 patients were enrolled. Among them 27(35.1%) were male and 50(64.9%) were female. The most common presenting complaint is itching followed by earache, ear discharge, hearing loss. Itching was present in 77.9% of the cases followed by earache in 72.7%, aural fullness in 29%, ear discharge in 46.8% and hearing loss in 31.2%. Based on type of fungal debris on otoscopy, blackish was the commonest with frequency of 38 patients (49.4%) followed by whitish debris in 27 patients (35.1%) and yellowish among 12 patients (15.6%). Conclusion: Otomycosis is one of the most common presenting problems in otorhinolaryngology OPD. Females are affected more. Aspergillus niger implicated the most and ear itching is the most common presenting symptom. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):20-24